OPTIMALISASI KETERLIBATAN PEMUDA SEBAGAI GENERASI PERUBAHAN DALAM SISTEM DEMOKRASI MELALUI PEMILIHAN UMUM 2024 - Vivi Frita Tresnani; Muhammad Dhafa Krisna Adhitya (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
The younger generation is a generation of change that must continue to fight and be able to manage the transition process of democracy towards a better direction, especially by overseeing the implementation of a just political process. The involvement of the younger generation is a crucial aspect in the sustainability of democracy. This research aims to understand the influence of the younger generation on the organization of the 2024 general election as a form of democracy and the role of the younger generation as agents of change in monitoring the 2024 general election. The research method uses a normative research approach, focusing on written laws or regulations and societal norms. Legal source materials include primary legal materials such as legislation, jurisprudence, court decisions, and official state documents, as well as secondary legal materials such as legal books and legal journals that contain fundamental principles. The research results indicate that the involvement and role of young people as change agents in a 2024 election within a democratic system need to be optimized from various aspects, including political participation, monitoring to prevent political corruption, advocacy and representation, voter education and socialization, technological literacy and social media, and as safeguards against election fraud, which would lead to a much better democracy.